2008
DOI: 10.1016/j.ejcts.2008.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Does radial use as a second arterial conduit for coronary artery bypass grafting improve long-term outcomes in diabetics?☆☆☆

Abstract: Using radial as a second arterial conduit as opposed to vein grafting did not confer a survival benefit in diabetics. This unexpected result is perhaps related to relatively diminished radial graft patency and/or the augmented radial vasoreactivity characteristic of diabetics. These findings indicate that the radial survival advantage demonstrated in the general CABG population lies primarily in non-diabetics in whom this advantage may be underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…This compared favorably with survival rates in historical series using mostly vein grafts in which patients were younger [7,8]. Although the subject is still a matter of controversy [9], the present study tends to confirm the protective effect of arterial grafting on survival as demonstrated by others [10,11]. The preferential use of arterial grafts including the radial artery in this series allowed relieving symptoms of myocardial ischemia in 80% of the cases and nearly abolished the risk for acute myocardial infarction (2.1%) over a 20-year follow-up period.…”
Section: Discussionsupporting
confidence: 84%
“…This compared favorably with survival rates in historical series using mostly vein grafts in which patients were younger [7,8]. Although the subject is still a matter of controversy [9], the present study tends to confirm the protective effect of arterial grafting on survival as demonstrated by others [10,11]. The preferential use of arterial grafts including the radial artery in this series allowed relieving symptoms of myocardial ischemia in 80% of the cases and nearly abolished the risk for acute myocardial infarction (2.1%) over a 20-year follow-up period.…”
Section: Discussionsupporting
confidence: 84%
“…Given the potential interdependence of transfusion and postoperative morbidity, comparisons were repeated after stratifying patients as having (complication) versus not having (no complication) any of the postoperative complications in the STS database. The operative technique and perioperative management were previously described [20].…”
Section: Patientsmentioning
confidence: 99%
“…The index operation was performed as previously described [17]. Post-CABG coronary angiograms were obtained at the discretion of the patients' cardiologists based on the development of symptoms suggestive of myocardial ischemia.…”
Section: Methodsmentioning
confidence: 99%